Factors Predictive of Proximal Disease Extension and Clinical Course of Patients Initially Diagnosed with Ulcerative Proctitis in an IBD Referral Center - da Costa Ferreira, Sandro; Otoboni Aprile, Lilian Rose; Parra, Rogério Serafim; Feitosa, Marley Ribeiro; da Silva Perdoná, Gleici de Castro; Féres, Omar; Ribeiro da Rocha, José Joaquim; de Almeida Troncon, Luiz Ernesto (Turkish Journal of Gastroenterology, 2022)
Background: This study aims to determine whether risk factors at the time of diagnosis that are found to be predictive of proximal disease extension in ulcerative proctitis (UP) occur in a cohort of Brazilian patients.Methods: This is a retrospective analysis of data from 97 patients (67% female) with UP (Montreal classification: E1) with at least12 months of follow-up who were admitted to the Ribeirão Preto Medical School IBD referral center between January 2001 and December2018. Proximal disease extension, which was defined as E1 progressing to E3 (pancolitis), was evaluated endoscopically during follow-up.Results: A total of 29 (29.9%) patients experienced proximal disease extension. The risk factors at diagnosis associated with proximaldisease extension were younger age (<40 years; P = .012), higher Mayo endoscopic score (P < .0001), higher partial Mayo score (P =.0018), and use of oral corticosteroids (P = .0016). During the follow-up period, increased disease relapse rates (P < .0001), immunomodulators (P = .00014) or the use of biological agents (P = .00037), and colectomy (P = .0002) were all significantly higher among UPpatients with proximal disease extension.Conclusion: Similar to what has been demonstrated in other studies, Brazilian UP patients with increased clinical and endoscopic severity at the time of diagnosis are likely to evolve with both proximal extension and a more adverse clinical course. Therefore, these patientsshould be followed-up more carefully.